Polyimide modified thermoplastic polyurethane composite conductive foam as well as preparation method and application thereof

By combining modified thermoplastic polyurethane with conductive materials and polyamic acid, combined with defoaming, coating film formation, salting and thermal imidation, composite conductive bubbles with better mechanical, conductive and heat-resistant properties are prepared. Cotton solves the problem of insufficient performance of traditional conductive foam in high temperature environments.

CN119431869APending Publication Date: 2025-02-14SHENZHEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411800013.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing conductive foams have shortcomings in mechanical properties, electrical conductivity and heat resistance, and may soften or lose strength in high temperature environments.

Method used

By mixing thermoplastic polyurethane with conductive material, polyamic acid and pore-forming agent, and by defoaming, coating and film formation, salting treatment and thermal imidation reaction, a composite of polyimide modified thermoplastic polyurethane is prepared by mixing thermoplastic polyurethane with conductive material, polyamic acid and pore-forming agent, and through defoaming, coating and film formation, salting treatment and thermal imidation reaction, a composite of polyimide modified thermoplastic polyurethane is Conductive foam.

Benefits of technology

The mechanical properties, electrical conductivity and heat resistance of composite conductive foam are significantly improved, so that it can remain stable under a high temperature environment of 260℃ and has better application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431869A_ABST
    Figure CN119431869A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of conductive foam, in particular to polyimide modified thermoplastic polyurethane composite conductive foam as well as a preparation method and application thereof. The preparation method comprises the following steps: dissolving thermoplastic polyurethane in a solvent to prepare a first solution, and then adding a conductive material, polyamide acid and a pore-forming agent to prepare a mixed solution; defoaming and coating the mixed solution to form a film, so as to obtain a composite material; and carrying out salting-out treatment on the composite material, and then carrying out thermal imidization reaction to obtain the polyimide modified thermoplastic polyurethane composite conductive foam. The method is simple in preparation process, easy to operate, convenient and efficient, and the prepared modified composite conductive foam has better mechanical performance, conductivity and heat resistance, especially can tolerate a 260 DEG C high-temperature environment, and has a very good application prospect in electronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of conductive foam, and in particular to a composite conductive foam of polyimide-modified thermoplastic polyurethane and a preparation method and application thereof. Background Art

[0002] Conductive foam is a material with conductive properties and shock-absorbing and cushioning effects. It is usually a mixture of polyurethane foam and conductive materials. It has good conductive properties, anti-static, shock-absorbing and cushioning, and thermal insulation properties. It is widely used in electronics, automobiles, aviation and other fields.

[0003] With the advancement of science and technology, electronic devices that integrate lightweight, compression resistance, wearability and other characteristics are the development trend of the organic integration of people and information in the future, so higher and higher requirements are put forward for the performance of conductive foam. Thermoplastic polyurethane used in traditional conductive foam has good processability, excellent bending and stretching ability, chemical corrosion resistance and other properties, but it has the problems of poor elasticity and poor conductivity, and its own heat resistance is relatively poor. It cannot withstand excessively high temperatures and may soften or lose strength in high temperature environments.

[0004] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a composite conductive foam of polyimide-modified thermoplastic polyurethane and a preparation method and application thereof, aiming to solve the problems of poor elasticity, poor conductivity and poor heat resistance of the existing conductive foam.

[0006] The technical solution of the present invention is as follows:

[0007] The first aspect of the present invention provides a method for preparing a composite conductive foam of polyimide-modified thermoplastic polyurethane, which comprises the steps of:

[0008] S1, dissolving thermoplastic polyurethane in a solvent to prepare a first solution, and then adding a conductive material, polyamic acid and a pore-forming agent to prepare a mixed solution;

[0009] S2, degassing and coating the mixed solution to form a film to obtain a composite material;

[0010] S3, subjecting the composite material to a salting-out treatment, and then subjecting it to a thermal imidization reaction, to obtain the composite conductive foam of the polyimide-modified thermoplastic polyurethane.

[0011] Optionally, the solvent is one or more of N-methylpyrrolidone, N,N-dimethylformamide and dimethyl sulfoxide, and the mass ratio of the thermoplastic polyurethane to the solvent is 1:3-4.

[0012] Optionally, in the mixed solution, the mass ratio of thermoplastic polyurethane, conductive material, polyamic acid and pore-forming agent is 1:0.1-0.25:0.25-1.25:1-8.

[0013] Optionally, the conductive material is one or more of conductive carbon black, two-dimensional layered nanomaterials, carbon nanotubes, silver nanowires, and nano-silver powder.

[0014] Optionally, the pore-forming agent is one or more of sodium chloride, glucose, sodium bicarbonate, and polymethyl methacrylate microspheres, and the particle size of the pore-forming agent is 100 to 400 meshes.

[0015] Optionally, in step S2, the degassing conditions include: centrifugation at a rotation speed of 300-600 rpm for 30-180 s, centrifugation at a rotation speed of 1500-2100 rpm for 120-300 s, and centrifugation at a rotation speed of 900-1400 rpm for 30-180 s;

[0016] The coating and film-forming conditions include: using a knife coating method to coat the film in a coating machine.

[0017] Optionally, in step S3, the salting-out treatment conditions include: in a water bath, the salting-out temperature is 40 to 80° C., and the salting-out time is 2 to 24 h;

[0018] The conditions of the thermal imidization reaction include: the thermal imidization temperature is 100 to 180° C., and the thermal imidization time is 0.5 to 6 hours.

[0019] Optionally, after the coating and film formation in step S2, a drying step is further included, wherein the drying temperature is 40 to 80° C. and the drying time is 1 to 24 hours;

[0020] After the salting-out treatment in step S3 and before the thermal imidization reaction, a drying step is further included, wherein the drying temperature is 80 to 100° C. and the drying time is 0.5 to 2 hours.

[0021] The second aspect of the present invention provides a composite conductive foam of polyimide-modified thermoplastic polyurethane, wherein the composite conductive foam is prepared by the preparation method of the composite conductive foam of polyimide-modified thermoplastic polyurethane described in the present invention.

[0022] The third aspect of the present invention provides an application of the composite conductive foam of polyimide-modified thermoplastic polyurethane of the present invention in electronic devices.

[0023] Beneficial effects: The present invention provides a method for preparing a composite conductive foam of polyimide-modified thermoplastic polyurethane. The method has a simple preparation process, is easy to operate, convenient and efficient. The prepared modified composite conductive foam has better mechanical properties, conductive properties and heat resistance, especially can withstand a high temperature environment of 260°C, and has good application prospects in electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The present invention provides a flow chart of a method for preparing a composite conductive foam of polyimide-modified thermoplastic polyurethane.

[0025] Figure 2 This is a physical picture of the TPU / PI composite conductive foam prepared in Example 1.

[0026] Figure 3 The graph is a relationship between compression strain and stress of the TPU / PI composite conductive foam prepared in Examples 1 to 3 and the TPU conductive foam prepared in Comparative Example 1.

[0027] Figure 4 This is a comparison diagram of the material morphology of the TPU / PI composite conductive foam prepared in Examples 1 to 3 and the TPU conductive foam prepared in Comparative Example 1 before and after the heat resistance test. DETAILED DESCRIPTION

[0028] The present invention provides a composite conductive foam of polyimide-modified thermoplastic polyurethane and a preparation method and application thereof. To make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0029] like Figure 1 As shown, an embodiment of the present invention provides a method for preparing a composite conductive foam of polyimide-modified thermoplastic polyurethane, which comprises the steps of:

[0030] S1, dissolving thermoplastic polyurethane in a solvent to prepare a first solution, and then adding a conductive material, polyamic acid and a pore-forming agent to prepare a mixed solution;

[0031] S2, degassing and coating the mixed solution to form a film to obtain a composite material;

[0032] S3, subjecting the composite material to a salting-out treatment, and then subjecting it to a thermal imidization reaction, to obtain the composite conductive foam of the polyimide-modified thermoplastic polyurethane.

[0033] In the embodiment of the present invention, thermoplastic polyurethane (TPU) is first dissolved in a solvent to prepare a TPU elastomer solution (first solution), and then a conductive material, polyamic acid (PAA) and a pore-forming agent are added to prepare a composite conductive elastomer mixed solution, and then the bubbles in the mixed solution are removed by a degassing operation to improve the consistency and uniformity of the sample, and a film-forming operation is performed to obtain a formed thin film composite material, and then the composite material is subjected to a salting-out treatment, wherein the pore-forming agent in the composite material is precipitated to form holes in the composite material, and finally the polyamic acid (PAA) in the composite material is converted into polyimide (PI) by a thermal imidization reaction to achieve the modification purpose, and finally the composite conductive foam (modified composite conductive foam) of the polyimide-modified thermoplastic polyurethane is obtained. The modified composite conductive foam prepared by the method has better mechanical properties, conductive properties and heat resistance, especially can withstand a high temperature environment of 260°C, and has a good application prospect in electronic devices.

[0034] The preparation method provided by the embodiment of the present invention has at least the following two advantages: (1) Based on the method of physical blending modification and thermal imidization, TPU and PI are innovatively fused to prepare a composite conductive foam of polyimide-modified thermoplastic polyurethane. Compared with the conventional conductive foam of thermoplastic polyurethane, the composite conductive foam has greatly improved mechanical properties, significantly improved heat resistance temperature and greatly improved conductivity, and also enhances the chemical stability of the material. (2) The pore-forming agent is first introduced into the composite material by a sacrificial template method, and then the pore-forming agent is precipitated by salting out to form holes in the composite material. The method is convenient for controlling the material size and nanostructure, reduces the difficulty of operation, and is easy to expand the production scale.

[0035] In some embodiments, the solvent is one or more of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO).

[0036] In some embodiments, the mass ratio of the thermoplastic polyurethane to the solvent is 1:3-4 to prepare a thermoplastic polyurethane elastomer solution.

[0037] In some embodiments, in the mixed solution, the mass ratio of thermoplastic polyurethane, conductive material, polyamic acid and pore former is 1: 0.1-0.25 (for example, 0.1, 0.2, 0.25): 0.25-1.25 (for example, 0.25, 0.5, 1.25): 1-8 (for example, 1, 1.5, 2, 2.5, 3, 4, 5, 6, 7, 8). The amount ratio of the raw materials is controlled based on the viscosity of the mixed solution. If the viscosity is too high, the mixing is uneven, and if the viscosity is too low, it is difficult to form a film. Within this range, a mixed solution with a suitable solution viscosity can be prepared so that a uniform composite film can be obtained later.

[0038] In some embodiments, the conductive material is one or more of conductive carbon black, two-dimensional layered nanomaterial (Mxene), carbon nanotube (CNT), silver nanowire, and nano silver powder.

[0039] In some embodiments, the pore former is one or more of sodium chloride, glucose, sodium bicarbonate, and polymethyl methacrylate microspheres (PMMA microspheres), and the particle size of the pore former is 100 to 400 meshes. The pore former is used to form pores in the modified composite conductive foam material. The pore former is first introduced into the composite material, and then the pore former is precipitated by salting out to form holes in the composite material. The purpose is to improve the mechanical properties of the material and increase the toughness of the material on the one hand, and to increase the resistance change space and improve the conductive performance on the other hand. The size and structure of the conductive foam material can be regulated by using pore formers of different types and sizes.

[0040] In some embodiments, the pore-forming agent is sodium chloride powder with a particle size of 100 to 400 mesh (eg, 100 mesh, 200 mesh, 300 mesh, 400 mesh).

[0041] In some implementations, the step S1 specifically includes:

[0042] Thermoplastic polyurethane is dissolved in a solvent to prepare a first solution, a conductive material is dissolved in a solvent to prepare a second solution, the first solution and the second solution are mixed with a polyamic acid solution to obtain a third solution, and a pore-forming agent is added thereto to obtain a mixed solution.

[0043] In this embodiment, the thermoplastic polyurethane, the conductive material and the polyamic acid are prepared into solutions respectively and then mixed, so that the materials can be better dispersed to obtain a uniform mixed solution.

[0044] In some embodiments, in step S2, the degassing conditions include: centrifugation at a rotation speed of 300-600 rpm for 30-180 s, centrifugation at a rotation speed of 1500-2100 rpm for 120-300 s, and centrifugation at a rotation speed of 900-1400 rpm for 30-180 s. Preferably, the degassing conditions include: centrifugation at a rotation speed of 600 rpm for 30 s, then centrifugation at a rotation speed of 1800 rpm for 240 s, and then centrifugation at a rotation speed of 1200 rpm for 30 s. Under the centrifugal degassing conditions, the bubbles in the mixed solution can be well removed to ensure the consistency and uniformity of the modified composite conductive foam material finally obtained.

[0045] In some embodiments, in step S2, the film-forming coating conditions include: using a doctor blade coating method to perform film-forming coating in a coating machine. The film-forming coating operation converts the mixed solution into a formed thin film composite material.

[0046] In some embodiments, after the coating and film forming in step S2, a drying step is also included, and the drying temperature is 40-80°C (for example, 40°C, 50°C, 60°C, 70°C, 80°C), and the time is 1-24h (for example, 1h, 5h, 10h, 11h, 12h, 13h, 14h, 15h, 20h, 24h).

[0047] In some embodiments, in step S3, the conditions for the salting-out treatment include: in a water bath, the salting-out temperature is 40-80°C (for example, 40°C, 50°C, 60°C, 70°C, 80°C), and the salting-out time is 2-24h (for example, 2h, 5h, 10h, 15h, 20h, 24h).

[0048] In some embodiments, in step S3, the conditions of the thermal imidization reaction include: a thermal imidization temperature of 100 to 180°C (for example, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C), and a thermal imidization time of 0.5 to 6h (for example, 0.5h, 1h, 2h, 3h, 4h, 5h, 6h).

[0049] In some embodiments, after the salting-out treatment in step S3 and before the thermal imidization reaction, a drying step is further included, wherein the drying temperature is 80-100° C. (e.g., 80° C., 90° C., 100° C.) and the drying time is 0.5-2 h (e.g., 0.5 h, 1 h, 1.5 h, 2 h).

[0050] The embodiment of the present invention provides a composite conductive foam of polyimide-modified thermoplastic polyurethane, wherein the composite conductive foam is prepared by the preparation method of the composite conductive foam of polyimide-modified thermoplastic polyurethane described in any of the above embodiments. The composite conductive foam of polyimide-modified thermoplastic polyurethane has better mechanical properties, conductive properties and heat resistance, especially can withstand high temperature environment of 260°C, and has good application prospects in electronic devices.

[0051] In some embodiments, the composite conductive foam of polyimide-modified thermoplastic polyurethane comprises thermoplastic polyurethane, polyimide and a conductive material.

[0052] An embodiment of the present invention provides an application of the composite conductive foam of polyimide-modified thermoplastic polyurethane described in the above embodiment in an electronic device.

[0053] The present invention will be further described below by means of specific examples.

[0054] Example 1

[0055] This embodiment provides a method for preparing a composite conductive foam of polyimide-modified thermoplastic polyurethane (TPU / PI composite conductive foam), comprising the following steps:

[0056] (1) adding thermoplastic polyurethane (TPU) to N-methylpyrrolidone (NMP), and mechanically stirring at 350 rpm for 2 h until the solution becomes clear and transparent, thereby obtaining a thermoplastic polyurethane solution, wherein the mass ratio of TPU to NMP is 1:3; dispersing conductive carbon black in NMP to obtain a conductive carbon black solution, wherein the mass ratio of conductive carbon black to NMP is 1:15;

[0057] (2) adding a polyamic acid (PAA) solution and a conductive carbon black solution into a thermoplastic polyurethane solution to obtain a TPU / PAA composite conductive solution, wherein the mass ratio of TPU: conductive carbon black: PAA is 1:0.2:0.25;

[0058] (3) adding 300-mesh sodium chloride (NaCl) powder to the TPU / PAA composite conductive solution under stirring, and stirring to obtain a TPU / PAA / NaCl composite conductive solution, wherein the mass ratio of TPU to NaCl powder is 1:2.5;

[0059] (4) placing the TPU / PAA / NaCl composite conductive solution into a planetary centrifuge for degassing, wherein the degassing conditions are centrifugation at a rotation speed of 600 rpm for 30 seconds, then centrifugation at a rotation speed of 1800 rpm for 240 seconds, and then centrifugation at a rotation speed of 1200 rpm for 30 seconds; placing the degassed TPU / PAA / NaCl composite conductive solution into a coating machine, applying a 4 mm coating film using a doctor blade method, and drying at 80° C. for 12 hours to obtain a TPU / PAA / NaCl composite material;

[0060] (5) Take out the dried TPU / PAA / NaCl composite material, put it into a water bath and perform salting at 60°C for 2h; dry it at 80°C for 30min; perform thermal imidization reaction at 150°C for 30min to obtain TPU / PI composite conductive foam, as shown in the figure. Figure 2 shown.

[0061] Example 2

[0062] The preparation method of Example 2 is the same as that of Example 1, except that the amount of PAA is changed in step (2). Step (2) is specifically as follows: a polyamic acid (PAA) solution and a conductive carbon black solution are added to a thermoplastic polyurethane solution to obtain a TPU / PAA composite conductive solution, wherein the mass ratio of TPU: conductive carbon black: PAA is 1:0.2:0.5; and finally a TPU / PI composite conductive foam is prepared.

[0063] Example 3

[0064] The preparation method of Example 3 is the same as that of Example 1, except that the amount of PAA is changed in step (2). Step (2) is specifically as follows: a polyamic acid (PAA) solution and a conductive carbon black solution are added to a thermoplastic polyurethane solution to obtain a TPU / PAA composite conductive solution, wherein the mass ratio of TPU: conductive carbon black: PAA is 1:0.2:1.25; and finally a TPU / PI composite conductive foam is prepared.

[0065] Example 4

[0066] The preparation method of Example 4 is the same as that of Example 1, except that in step (3), the particle size of the sodium chloride powder is adjusted to 200 mesh and the amount of the sodium chloride powder is changed. Step (3) is specifically as follows: under stirring, adding 200 mesh sodium chloride powder to the TPU / PAA composite conductive solution, stirring to obtain a TPU / PAA / NaCl composite conductive solution, wherein the mass ratio of TPU to NaCl powder is 1:5; and finally preparing a TPU / PI composite conductive foam.

[0067] Example 5

[0068] The preparation method of Example 5 is the same as that of Example 4, except that the amount of PAA is changed in step (2). Step (2) is specifically as follows: adding a polyamic acid (PAA) solution and a conductive carbon black solution to a thermoplastic polyurethane solution to obtain a TPU / PAA composite conductive solution, wherein the mass ratio of TPU: conductive carbon black: PAA is 1:0.2:0.5; and finally, a TPU / PI composite conductive foam is prepared.

[0069] Comparative Example 1

[0070] This comparative example provides a method for preparing a thermoplastic polyurethane composite conductive foam (TPU composite conductive foam), comprising the following steps:

[0071] (1) adding thermoplastic polyurethane (TPU) to N-methylpyrrolidone (NMP), and mechanically stirring at 350 rpm for 2 h until the solution becomes clear and transparent, thereby obtaining a thermoplastic polyurethane solution, wherein the mass ratio of TPU to NMP is 1:3; dispersing conductive carbon black in NMP to obtain a conductive carbon black solution, wherein the mass ratio of conductive carbon black to NMP is 1:15;

[0072] (2) mixing a thermoplastic polyurethane solution and a conductive carbon black solution to obtain a TPU composite conductive solution, wherein the mass ratio of TPU to conductive carbon black is 1:0.2;

[0073] (3) adding 300-mesh sodium chloride (NaCl) powder to the TPU composite conductive solution under stirring, and stirring to obtain a TPU / NaCl composite conductive solution, wherein the mass ratio of TPU to sodium chloride powder is 1:2.5;

[0074] (4) placing the TPU / NaCl composite conductive solution into a planetary centrifuge for degassing, wherein the degassing conditions are centrifugation at a rotation speed of 600 rpm for 30 seconds, then centrifugation at a rotation speed of 1800 rpm for 240 seconds, and then centrifugation at a rotation speed of 1200 rpm for 30 seconds; placing the degassed TPU / NaCl composite conductive solution into a coating machine, applying a 4 mm coating film using a doctor blade method, and drying at 80° C. for 12 hours to obtain a TPU / NaCl composite material;

[0075] (5) The dried TPU / NaCl composite material was taken out, placed in a water bath at 60° C. for salting out for 2 h, and dried at 80° C. for 30 min to obtain TPU conductive foam.

[0076] Comparative Example 2

[0077] The preparation method of Comparative Example 2 is the same as that of Comparative Example 1, except that in step (3), the particle size of the sodium chloride powder is adjusted to 200 mesh and the amount of the sodium chloride powder is changed. Step (3) is specifically as follows: under stirring, adding 200 mesh sodium chloride powder to the TPU composite conductive solution, stirring to obtain a TPU / NaCl composite conductive solution, wherein the mass ratio of TPU to NaCl powder is 1:5; and finally preparing TPU conductive foam.

[0078] Performance Testing:

[0079] (1) The conductivity of the TPU / PI composite conductive foam prepared in Examples 1 to 5 and the TPU conductive foam prepared in Comparative Examples 1 to 2 was tested. The specific method was to use Instrument 6500 for testing, cut the sample to be tested into a fixed size, treat both ends with conductive silver paste (baked at 80°C for 30 min), use the ohm position of the digital source meter to record the resistance, and calculate the resistivity and conductivity according to the resistivity formula derived from Ohm's law. After multiple measurements, the average value of the resistivity and conductivity was taken.

[0080] The resistivity and conductivity data of the TPU / PI composite conductive foams prepared in Examples 1 to 5 and the TPU conductive foams prepared in Comparative Examples 1 to 2 are shown in Table 1.

[0081] Table 1

[0082] Resistivity (Ω·m) Conductivity (S / m) Example 1 0.188 5.325 Example 2 0.202 4.956 Example 3 0.253 3.957 Comparative Example 1 0.383 2.610 Example 4 1.868 0.535 Example 5 1.464 0.683 Comparative Example 2 2.304 0.434

[0083] It can be seen from the data in Table 1 that, relative to the TPU conductive foam in Comparative Examples 1 to 2, the TPU / PI composite conductive foam prepared by the preparation method of the present invention has lower resistivity and higher conductivity, that is, has better conductive properties, indicating that the TPU / PI composite conductive foam prepared by the present invention significantly improves the conductivity of the TPU conductive foam.

[0084] (2) Mechanical properties of the TPU / PI composite conductive foam prepared in Examples 1 to 3 and the TPU conductive foam prepared in Comparative Example 1 were tested. The specific method was to use a universal mechanical testing machine Instron ElectroPuls to cut the sample to be tested into 4×6×1 mm 3 The cube is fixed on the test bench, and the corresponding compressive stress-compressive strain is obtained through compression test, and a relationship curve graph between compressive strain and stress is obtained.

[0085] Figure 3 The graph is a relationship curve between the compression strain and stress of the TPU / PI composite conductive foam prepared in Examples 1 to 3 and the TPU conductive foam prepared in Comparative Example 1. It can be seen from the graph that the modulus of the TPU / PI composite conductive foam prepared in Examples 1 to 3 is greater than that of the TPU conductive foam without PI in Comparative Example 1. Compared with Comparative Example 1, Examples 1 and 2 enter the linear elastic region at 40% strain, Example 2 enters the linear elastic region at 50% strain, and Comparative Example 1 enters the linear elastic region at 55% strain. Therefore, the linear elastic region of Comparative Example 1 is smaller than that of Examples 1 and 2. In addition, compared with Comparative Example 1, in its linear elastic region, Example 3 has an elastic modulus slightly greater than that of Comparative Example 1.

[0086] (3) The heat resistance of the TPU / PI composite conductive foam prepared in Examples 1 to 3 and the TPU conductive foam prepared in Comparative Example 1 was tested. The specific method was to select a sample of appropriate size and put it into a blast drying oven, and heat it from room temperature to 260°C at a rate of 5°C / min and keep it for 30 minutes, then take it out and observe the material morphology.

[0087] Figure 4 3 is a comparison diagram of the material morphology of the TPU / PI composite conductive foam prepared in Examples 1 to 3 and the TPU conductive foam prepared in Comparative Example 1 before and after the heat resistance test, wherein Figure 4Figure a and Figure b are material morphology diagrams of the TPU / PI composite conductive foam of Example 1 before and after the heat resistance test, respectively, Figure c and Figure d are material morphology diagrams of the TPU / PI composite conductive foam of Example 2 before and after the heat resistance test, respectively, Figure e and Figure f are material morphology diagrams of the TPU / PI composite conductive foam of Example 3 before and after the heat resistance test, Figure g and Figure h are material morphology diagrams of the TPU conductive foam of Comparative Example 1 before and after the heat resistance test, respectively. It can be seen from the figure that the TPU / PI composite conductive foams of Examples 1 to 3 did not decompose and crack after experiencing a high temperature of 260°C, and still maintained their original shape, and had good high temperature resistance; while the TPU conductive foam of Comparative Example 1 decomposed and cracked after experiencing a high temperature of 260°C, could not maintain its original shape, and had no high temperature resistance at all.

[0088] In summary, the present invention provides a method for preparing a composite conductive foam of polyimide-modified thermoplastic polyurethane, wherein TPU is first prepared into a solution, and then a conductive material, a PAA solution and a pore-forming agent are added thereto to obtain a mixed solution, and then a modified composite conductive foam with good performance is obtained after degassing, coating film formation, salting out pore formation, thermal imidization reaction and other steps. The method has a simple preparation process, is easy to operate, convenient and efficient, and the prepared modified composite conductive foam has better mechanical properties, conductive properties and heat resistance, especially can withstand a high temperature environment of 260°C, and has a good application prospect in electronic devices.

[0089] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing a composite conductive foam of polyimide-modified thermoplastic polyurethane, characterized in that: Includes steps: S1, dissolving thermoplastic polyurethane in a solvent to prepare a first solution, and then adding a conductive material, polyamic acid and a pore-forming agent to prepare a mixed solution; S2, degassing and coating the mixed solution to form a film to obtain a composite material; S3, subjecting the composite material to a salting-out treatment, and then subjecting it to a thermal imidization reaction, to obtain the composite conductive foam of the polyimide-modified thermoplastic polyurethane.

2. The method for preparing the composite conductive foam of polyimide-modified thermoplastic polyurethane according to claim 1, characterized in that: The solvent is one or more of N-methylpyrrolidone, N,N-dimethylformamide and dimethyl sulfoxide, and the mass ratio of the thermoplastic polyurethane to the solvent is 1:3-4.

3. The method for preparing the composite conductive foam of polyimide-modified thermoplastic polyurethane according to claim 1, characterized in that: In the mixed solution, the mass ratio of thermoplastic polyurethane, conductive material, polyamic acid and pore-forming agent is 1:0.1-0.25:0.25-1.25:1-8.

4. The method for preparing the composite conductive foam of polyimide-modified thermoplastic polyurethane according to claim 1, characterized in that: The conductive material is one or more of conductive carbon black, two-dimensional layered nanomaterials, carbon nanotubes, silver nanowires, and nano silver powder.

5. The method for preparing the composite conductive foam of polyimide-modified thermoplastic polyurethane according to claim 1, characterized in that: The pore-forming agent is one or more of sodium chloride, glucose, sodium bicarbonate, and polymethyl methacrylate microspheres, and the particle size of the pore-forming agent is 100-400 meshes.

6. The method for preparing the composite conductive foam of polyimide-modified thermoplastic polyurethane according to claim 1, characterized in that: In step S2, the degassing conditions include: centrifugation at a rotation speed of 300-600 rpm for 30-180 s, centrifugation at a rotation speed of 1500-2100 rpm for 120-300 s, and centrifugation at a rotation speed of 900-1400 rpm for 30-180 s; The coating and film-forming conditions include: using a knife coating method to coat the film in a coating machine.

7. The method for preparing the composite conductive foam of polyimide-modified thermoplastic polyurethane according to claim 1, characterized in that: In step S3, the salting-out treatment conditions include: in a water bath, the salting-out temperature is 40 to 80° C., and the salting-out time is 2 to 24 hours; The conditions of the thermal imidization reaction include: the thermal imidization temperature is 100 to 180° C., and the thermal imidization time is 0.5 to 6 hours.

8. The method for preparing the composite conductive foam of polyimide-modified thermoplastic polyurethane according to claim 1, characterized in that: After the coating and film formation in step S2, a drying step is also included, wherein the drying temperature is 40 to 80° C. and the drying time is 1 to 24 hours; After the salting-out treatment in step S3 and before the thermal imidization reaction, a drying step is further included, wherein the drying temperature is 80 to 100° C. and the drying time is 0.5 to 2 hours.

9. A composite conductive foam of polyimide-modified thermoplastic polyurethane, characterized in that: The composite conductive foam is prepared by the method for preparing the composite conductive foam of polyimide-modified thermoplastic polyurethane as described in any one of claims 1 to 8.

10. Use of the composite conductive foam of polyimide-modified thermoplastic polyurethane as claimed in claim 9 in electronic devices.